2022
DOI: 10.1097/mcg.0000000000001810
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Radiofrequency Ablation Plus Stent Versus Stent-alone Treatments for Malignant Biliary Strictures

Abstract: Background/Aims: Malignant biliary strictures (MBS) are very aggressive and cannot be diagnosed in the early stages due to their asymptomatic nature. Stenting the stricture area of the biliary tree is palliative treatment but has poor survival time. Radiofrequency ablation plus stent (RFA+S) have been recently used to improve the survival and stent patency time in patients with MBS. In this systematic review and meta-analysis, we tried to evaluate the efficacy and safety of radiofrequency ablation. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…These factors are critically important to accurately assess stent patency, especially when studying such a heterogeneous population. Another meta-analysis included duplicate data, which also limited interpretability of the results [30]. Our current systematic and metaanalysis is strengthen by including only RCTs, and thus, presents the highest evidence level.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These factors are critically important to accurately assess stent patency, especially when studying such a heterogeneous population. Another meta-analysis included duplicate data, which also limited interpretability of the results [30]. Our current systematic and metaanalysis is strengthen by including only RCTs, and thus, presents the highest evidence level.…”
Section: Discussionmentioning
confidence: 93%
“…Four previous meta-analyses have investigated stent patency comparing groups with and without RFA; however, there have been discrepant results [27][28][29][30]. In these prior meta-analyses, most eligible studies were observational or retrospective; there were few numbers of RCTs, and limited data regarding type of stent utilized, treatment route (endoscopic or percutaneous), tumor location, and etiology of MBO.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses have confirmed that RFA does not increase the additional risk of adverse events compared to conventional ERCP. [32][33][34][35]61 However, it may still lead to certain complications; therefore, sufficient attention should be paid to and active prevention and treatment should be taken for high-risk patients.…”
Section: Prevention and Treatment Of Complications In Endobiliary Rfamentioning
confidence: 99%
“…34 In a meta-analysis, there was no statistical difference in the occurrence of abdominal pain between the RFA group and the stenting alone group (risk ratio [RR] 1.06, 95% CI 0.79-1.40, P = 0.71). 61 Generally, abdominal pain lasts for 1-5 days and can be relieved spontaneously, and analgesics can be given when necessary. Other rare complications include partial liver infarction, 68 biliary duct perforation, 69 liver abscess, 23 and bile leakage, 63 which are related to the thermal effect of RFA that affects local blood vessels as well as deep tissue damage.…”
Section: Other Complicationsmentioning
confidence: 99%
See 1 more Smart Citation